ON THE ISSUE OF THE ELEMENTS OF THE ECONOMIC MECHANISM OF ENVIRONMENTAL PROTECTION AND NATURE MANAGEMENT IN THE EAEU COUNTRIES - K. Kolesnikova; T. Makarova (Гуманитарные и юридические исследования)
The article examines the current issues of legal regulation of the economic mechanism of environmental protection and rational use of natural resources in the member states of the EAEU, which includes various tools that have speciic features and forms of implementation in each member country. The article analyzes the norms of the legislation of the Russian Federation, the Republic of Kazakhstan, the Republic of Belarus, the Republic of Armenia, regulating the establishment of both tax and non-tax payments for the use of natural resources and the provision of various types of impacts on the natural environment. The legal nature of payment for negative impact on the environment, environmental tax, emissions into the environment is considered in detail. The author gives an assessment of the effectiveness of these legal instruments for the purposes of maintaining environmental safety and sustainable use of natural resources. Various approaches to the implementation of the environmental function of states are analyzed in the article, this function requires a competent combination of administrative, economic and market mechanisms, in order to mitigate the impact on the economy with increasing costs for achieving the accepted standards of environmental quality and ensuring the rational use of natural resources. The author advocates the need for harmonization environmental legislation, speciically in terms of creating environmental funds by all EAEU member states, which will allow implementing the compensatory function of environmental payments, which is expressed in their correlation with the amount of harm caused to the environment, by accumulating monetary assets in funds from various sources and their purposeful spending on environmentally signiicant activities. It is proposed to adopt regulatory legal acts at the level of the EAEU, the purpose of which would be the regulation of relations concerning environmental management and environmental protection, including inancing relations. This is especially relevant, taking into consideration the environmental challenges facing the world community, and the recent increase in man-made disasters. In addition to the regulatory framework, it is necessary to create supranational institutions and mechanisms for inancing the environmental sphere within the framework of the EAEU.